Case Studies in e-RPL and e-PR - Cameron, Roslyn; Miller, Alison (Adult Learning Australia Inc, 2014)
The use of ePortfolios for recognition of prior learning (e-RPL) and for professional recognition (e-PR) is slowly gaining in popularity in the VET sector however their use is sporadic across educational sectors, disciplines, educational institutions and professions. Added to this is an array of purposes and types of e-RPL and e-PR models and practice. The aim of this paper is to build on the conceptual framework developed by Cameron (2012) for e-RPL and e-PR and to provide case studies for each of the four types developed within this framework: e-PR for Professional Accreditation; e-RPL for Workplace Recognition; e-RPL for Access and; e-RPL for Self Recognition. We use the case studies to explore the four types and the two dimensions or continuums central to the framework. The vertical dimension is a continuum between RPL as process and RPL as product and the second horizontal dimension is a continuum between formal learning contexts and low learner control as opposed to informal learning contexts and high levels of learner control. The case studies have aided the further development of the framework and its theoretical and practical applications.